The Albanian Diaspora in Budzhak and Priazovye: A Problem of Language and Identity - Dugushina, Aleksandra (Journal on ethnopolitics and minority issues in Europe JEMIE, 2024)
The article analyses the problem of language and identity among the Albanian diaspora – an ethnic minority living along the Black Sea coast in the Budzhak region and the Azov Sea area in the Priazovye region. The paper outlines the history of Albanian settlements in Eastern Europe and traces various strategies for self-identification and the nuances of being an Albanian during different historical periods. In the last two decades of the 21st century, the Albanian diaspora has experienced a big rise in interest in the Albanian language, culture, and traditions. This surge has brought new group initiatives, a search for connections to the historical homeland, new ways of marking ethnic identity, and efforts to preserve the native language. Based on the author's field data, the research focuses on local ethnic activism and contemporary communication and “recognition” between representatives of the Albanian diaspora and Albanians from the Balkans. Particular attention is paid to the issue of the Albanian dialect and standard Albanian, which plays a significant role in the policy of integrating the Albanians of Budzhak and Priazovye into the transnational diaspora space.